Professional Care Workers’ Patterns of Occupational-Biographical Learning - Anna-Maria Kamin (Adult Education Research Conference, 2014)
This contribution explores the ways in which employees in medical and health care practice professionally relevant learning and what kind of significance digital media receive in this context. Therefore qualitative interviews with employees in various fields of medical and health care were analyzed and three characteristic occupational-biographical patterns of learning were carved out.